Uterine contractility in women whose fetus is delivered in the occipitoposterior position - Buhimschi, Catalin S.; Buhimschi, Irina A.; Malinow, Andrew M.; Weiner, Carl P. (American journal of obstetrics and gynecology, 2003)
Objective: Most fetuses in the occipitoposterior position rotate spontaneously after striking the pelvic floor. The increased prevalence of prolonged labor, operative delivery, and oxytocin augmentation in women with an occipitoposterior fetal position seems consistent with decreased uterine contractility. We sought to test the hypothesis that women with a persistent occipitoposterior fetal position have inadequate intrauterine pressure. Study Design: Intrauterine pressure was measured prospectively electronically in 94 women whose labor pain was controlled by patient-requested epidural analgesia. Eleven women (12%) were delivered as a persistent occipitoposterior fetal position. In a nested case-control study, these women were compared with 22 women who were delivered as an occipitoanterior fetal position who were matched for age, parity, gestational age, cervical examination at study enrollment, and body mass index. The intrauterine pressure measurements were initiated during the first stage of labor and continued throughout the entire labor process. Women were encouraged in the second stage of labor, after a period of recording baseline contractility, to push using a standardized Valsalva maneuver once the vertex reached the +2 station. The area under the intrauterine pressure curve (integral) was used to estimate uterine contractility and expulsive performances. Results: Five women (45%) in the occipitoposterior group required operative delivery. The average duration of the second stage of labor in the occipitoposterior group was 91.4 ± 23.2 minutes compared with 51.7 ± 6.6 minutes in the occipitoanterior fetal position (P =.04). Ninety percent of women in the occipitoposterior group required oxytocin, compared with 59% of the women in the occipitoanterior group (P =.11). There were no differences in uterine contractility between occipitoposterior and occipitoanterior groups during either the first stage of labor (integral mean ± SEM: occipitoposterior [1685.3 ± 194.6 mm Hg · s] vs occipitoanterior fetal position [1700.8 ± 128.9 mm Hg · s, P =.98]) or second stages of labor (occipitoposterior [1952.6 ± 186.5 mm Hg · s] vs occipitoanterior fetal position [1740.8 ± 104.3 mm Hg · s, P =.46]). Further, there were no significant differences in pushing performances between the occipitoposterior and occipitoanterior groups (Valsalva maneuver: occipitoposterior 2864.9 ± 328.8 mm Hg · s] vs occipitoanterior [2898.6 ± 222.2 mm Hg · s, P =.90]). Conclusion: Women who were delivered as a persistent occipitoposterior fetal position do not have lower intrauterine pressure levels immediately before or during the second stage of labor. (Am J Obstet Gynecol 2003;188:734-9.)